Influence of Drying Method and Argon Plasma Modification of Bacterial Nanocellulose on Keratinocyte Adhesion and Growth - Kutová, Anna; Staňková, Lubica; Vejvodová, Kristýna; Kvítek, Ondřej; Vokatá, Barbora; Fajstavr, Dominik; Kolská, Zdeňka; Brož, Antonín; Bačáková, Lucie; Švorčík, Václav (Nanomaterials (Basel, Switzerland), 2021)
Due to its nanostructure, bacterial nanocellulose (BC) has several advantages over plant cellulose, but it exhibits weak cell adhesion. To overcome this drawback, we studied the drying method of BC and subsequent argon plasma modification (PM). BC hydrogels were prepared using the Komagataeibacter sucrofermentans (ATCC 700178) bacteria strain. The hydrogels were transformed into solid samples via air-drying (BC-AD) or lyophilization (BC-L). The sample surfaces were then modified by argon plasma. SEM revealed that compared to BC-AD, the BC-L samples maintained their nanostructure and had higher porosity. After PM, the contact angle decreased while the porosity increased. XPS showed that the O/C ratio was higher after PM. The cell culture experiments revealed that the initial adhesion of human keratinocytes (HaCaT) was supported better on BC-L, while the subsequent growth of these cells and final cell population density were higher on BC-AD. The PM improved the final colonization of both BC-L and BC-AD with HaCaT, leading to formation of continuous cell layers. Our work indicates that the surface modification of BC renders this material highly promising for skin tissue engineering and wound healing.
Keywords: plasma modification; bacterial nanocellulose; lyophilization; cell adhesion